How Does Digital Marketing Drive Customer Attraction? Evidence From Traditional Msme - Latifah Rasidina Ayuning Saswianto; Ihwan Susila (Yayasan Riset dan Pengembangan Intelektual, 2026)
Traditional MSMEs often struggle with promotion due to budget constraints, making digital marketing a necessity to build attraction and survive. While quantitative data shows statistical success, in-depth understanding of how digital content builds consumer trust remains limited. This exploratory case study analyse the digital marketing strategies of a traditional cowhide cracker business, MSMEs in Sukoharjo, evaluating both consumer experiences and the owner’s perspective. Data were gathered over a two-week period via semi-structured in-depth interviews with the owner and consumers (loyal, new, and passive), digital observations on TikTok and Instagram, and documentation. Data validity was checked through source and technique triangulation, and analysed using Thematic Analysis. The results demonstrate that the MSME's consistent deployment of trend-based videos and interactive Q&A responses functions as an environmental Stimulus (S). Evaluated through Social Construction of Technology (SCOT) theory and the Stimulus-Organism-Response (S-O-R) model, these digital practices do not act deterministically; rather, they serve as a negotiated space where platform meanings are contested between the owner’s push for business survival and the consumer’s internal Organism (O) processing of trust and authenticity. Consumer attraction stabilizes into a positive behavioural Response (R) manifesting as purchase intentions and digital storefront transactions only when the aesthetic appeal of the content is met with functional clarity and structural product details. The study concludes that socially constructed digital stimuli successfully transform initial cognitive curiosity into long-term affective trust and conative purchasing actions.